2009
DOI: 10.1007/s00330-009-1653-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the anterior chamber depth of a globe on CT for detecting open-globe injury

Abstract: Change in the ACD is a helpful CT finding for detecting open-globe injury. A difference in the ACDs > or =0.4 mm is a helpful diagnostic criterion with excellent specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…16 Literature searches show that there is an agreement that CT scanning is the gold standard for imaging in the majority of trauma cases. 23 Kim et al 24 looked into the change of anterior chamber depth found on CT to aid in detecting an open-globe injury. This was found to be a helpful diagnostic criterion with a reported sensitivity of 92%, specificity of 85%, and diagnostic accuracy of 89%.…”
Section: Discussionmentioning
confidence: 99%
“…16 Literature searches show that there is an agreement that CT scanning is the gold standard for imaging in the majority of trauma cases. 23 Kim et al 24 looked into the change of anterior chamber depth found on CT to aid in detecting an open-globe injury. This was found to be a helpful diagnostic criterion with a reported sensitivity of 92%, specificity of 85%, and diagnostic accuracy of 89%.…”
Section: Discussionmentioning
confidence: 99%
“…Based on thin sliced CT, Kim et al [2] recommend the measurement of anterior chamber depth (posterior margin of the cornea to anterior margin of the lens should be measured in the midline of the tangent through the anterior lens). The authors found that a difference of the anterior chamber depth between the injured and non injured eye of more than 0.4 mm is a very helpful diagnostic criterion which carries excellent specificity.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Prompt diagnosis and surgical repair of the injury are crucial to optimize visual outcome. 4,5 There are only 2 predictive models of poor visual outcome after open globe injury, the Ocular Trauma Score system 6 and the Classification and Regression Tree model, that were developed to guide both clinicians and patients in clinical decision-making. 7 The Ocular Trauma Score is derived from presenting VA, globe rupture, endophthalmitis, perforating injury, retinal detachment, and relative afferent pupillary defect (RAPD) as predictors of poor visual outcome.…”
mentioning
confidence: 99%
“…9 In contemporary trauma care, CT has evolved as the imaging technique of choice for evaluating orbital trauma, especially in patients with difficult ophthalmologic examinations. 4,5,[8][9][10] Various studies have shown the sensitivities and specificities of CT, ranging from 56% to 76% and 79% to 100%, respectively, in detecting open globe injuries. 4,5,[8][9][10] CT offers the additional benefit of detecting concomitant intraorbital soft-tissue injuries and orbitofacial fractures.…”
mentioning
confidence: 99%
See 1 more Smart Citation